Understanding of organizational crises from the theory of social systems and from the perspective of the ambidextrous organization - Torres, Juan Pablo; Contreras-Illanes, Eduardo (Estudios de Administración, 2016)
The purpose of this article is to reflect about how organizational crisis can trigger organizational tensions based the theory of social system. Organizational tensions are problems related to balance decisions or group of decisions mutually exclusive. These tensions require executives to explore new opportunities even as they work diligently to exploit existing capabilities. The organizations that are willing to deal with these organizational tensions are considered as ambidextrous organizations. This article proposes a conceptual model to understand such tensions during organizational crisis.